2008
DOI: 10.4018/jisp.2008100105
|View full text |Cite
|
Sign up to set email alerts
|

Will it be Disclosure or Fabrication of Personal Information? An Examination of Persuasion Strategies on Prospective Employees

Abstract: Individuals are increasingly reluctant to disclose personal data and sometimes even intentionally fabricate information to avoid the risk of having it compromised. In such situations, , organizations face an acute dilemma: they must obtain accurate job applicant information in order to make good hiring decisions, but potential employees may be reluctant to provide accurate information because they fear it could be used for other purposes. Building on theoretical foundations from social cognition and persuasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
(65 reference statements)
0
11
0
1
Order By: Relevance
“…Users across the world are increasingly wary of Big Brother, and more so of Big Business as businesses amass and scrutinize more and more data about users [67]. It is observed that people have become increasingly reluctant to disclose their personal data and even resort to fabricating such information in order to mitigate the risk of abuse [83]. Research on privacy has modeled privacy concern in several different ways [131].…”
Section: Salient Belief-privacy Concernmentioning
confidence: 98%
“…Users across the world are increasingly wary of Big Brother, and more so of Big Business as businesses amass and scrutinize more and more data about users [67]. It is observed that people have become increasingly reluctant to disclose their personal data and even resort to fabricating such information in order to mitigate the risk of abuse [83]. Research on privacy has modeled privacy concern in several different ways [131].…”
Section: Salient Belief-privacy Concernmentioning
confidence: 98%
“…Prior studies in information system area show that information privacy concerns affect individuals' attitudes and willingness to purchase online (Milberg et al, 2000;Stewart and Segars, 2002;Dinev and Hart, 2006). As discussed in Li and Santhanam (2008), people who have high concerns about privacy may think it is risky to provide information and therefore may react negatively to requests for personal information. That is, they may be unwilling to disclose information or terminate the transaction.…”
Section: Taxpayers' Online Information Privacy Concerns and Behavior mentioning
confidence: 99%
“…In the privacy literature, a major research stream has emerged that uses intention-based theories such as theory of reasoned action (TRA) (Li and Santhanam, 2008;Liu et al, 2005;Malhotra et al, 2004) to predict outcomes of individuals' privacy concerns. According to these theories, the level of individuals' privacy concerns, as an attitude variable, has a negative effect on intentions to use internet-based services.…”
Section: Taxpayers' Online Information Privacy Concerns and Behavior mentioning
confidence: 99%
See 1 more Smart Citation
“…The diversification of options for collecting, processing, distributing and using personal information and the increase in the use of information processing technologies trigger consumer concerns (Belanger & Crossler, 2011). Consumers who are concerned about privacy issues may become increasingly reluctant to disclose their personal information and may even resort to fabricating this information to reduce the risk of abuse (Li & Santhanam, 2011;Bansal et al, 2016). This situation is explained by the concept of privacy concern (Malhotra et al, 2004;Awad & Krishnan, 2006;Dinev & Hart, 2006;Bansal et al, 2016).…”
Section: Information Privacy and Privacy Concernmentioning
confidence: 99%